Employment concentration and resource allocation: One-company towns in Russia - Simon Commander; Zlatko Nikoloski; Alexander Plekhanov (Institute for the Study of Labor (IZA), 2011)
The paper looks at the effects of employment concentration on resource allocation with a particular focus on one-company towns in Russia defined as towns where a single company accounts for a significant share of total employment of the locality. Empirical analysis of firms' production functions indicates that companies located in one-company towns are characterised by lower marginal product of labour, higher marginal product of capital and lower overall productivity pointing towards significant labour hoarding. One-company town enterprises are also found to be financially more vulnerable. The paper argues that the dominance of natural resources in the Russian economy and employment concentration is closely linked.
urn:nbn:de:101:1-201110263788
Keywords: D24; J42; R23; 330; employment concentration; one-company towns; labour productivity; Russia; Arbeitsmarkt; Beschäftigung; Unternehmenskonzentration; Regionales Cluster; Stadt; Russland